2022
DOI: 10.1186/s12883-022-02610-8
|View full text |Cite
|
Sign up to set email alerts
|

Cranial autonomic symptoms in migraine are related to central sensitization: a prospective study of 164 migraine patients at a tertiary headache center

Abstract: Background Cranial autonomic symptoms (CASs) during migraine attacks are reported to be quite common regardless of ethnicity. In our previous study investigating 373 migraineurs, we found that 42.4% of them had CASs. The patients with CASs more frequently had cutaneous allodynia than did those without CASs, and we speculated that CASs were associated with central sensitization. The present study searched for substantial evidence on the relationship between CASs and central sensitization in migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 30 publications
2
15
1
Order By: Relevance
“…These data [7,28] confirmes those coming from the clinical series [4][5][6][8][9][10][11][12][13][14][15][17][18][19][20][21][22][23][24][25][26][27]. Further the prevalence may be sometimes undervalued because some researches only look for the unilateral CAS while in clinical series they may be also present bilaterally as well as migraine pain may have bilateral lateralization.…”
Section: Epidemiological Pointsupporting
confidence: 76%
See 1 more Smart Citation
“…These data [7,28] confirmes those coming from the clinical series [4][5][6][8][9][10][11][12][13][14][15][17][18][19][20][21][22][23][24][25][26][27]. Further the prevalence may be sometimes undervalued because some researches only look for the unilateral CAS while in clinical series they may be also present bilaterally as well as migraine pain may have bilateral lateralization.…”
Section: Epidemiological Pointsupporting
confidence: 76%
“…Another study [27] evidenced that CAS+ migraineurs had significantly a greater central sensitization scored by the validated central sensitization inventory (CSI), suggesting a role of cranial parasympathetic activation to activate the central sensitization. This study support the Yarnitsky et al [38] study that suggested that the role of cranial parasympathetic outflow to sensitize the intracranial nociceptors and to induce parasympathetically indipendent allodynia by sensitizing central trigeminal nociceptors.…”
Section: Clinical Pointmentioning
confidence: 99%
“…The determinants of CS in migraine patients were restless legs syndrome and interference of headache pain with daily activities. Danno et al, 54 (2022) 164 patients with migraine A cross-sectional study using CSI CS was observed in 32.3% of migraine patients and was related to cranial parasympathetic symptoms such as lacrimation, aural fullness, nasal blockage, and rhinorrhea, Suzuki et al, 56 (2022) 95 patients with migraine A cross-sectional study using CSI and QEESI Multiple chemical sensitivity was found in 20% of migraine patients and was related to CS, photophobia, osmophobia, visual aura, sensory aura, higher migraine-related disability and Kessler Psychological Distress scores. Note : CSI scores ≥ 40 were defined as having CS.…”
Section: Methodsmentioning
confidence: 99%
“…For example, in a cross-sectional study including 164 patients with migraine, CS was observed in 53 patients (32.3%). 54 CS is associated with cranial parasympathetic symptoms such as lacrimation, aural fullness, nasal blockage, and rhinorrhea, suggesting that both trigeminovascular systems and the cranial parasympathetic system contribute to persistent CS in patients with migraine. MCS is reported to overlap with fibromyalgia, a disease known to be associated with CS.…”
Section: Methodsmentioning
confidence: 99%
“…Many of these “evahistic” manifestations can actually be the main symptom of the clinical picture in a patient with migraine, and imply a higher disability [ 5 ]. Migraine patients with sensory hypersensitivity may have more attention difficulties during daily activities [ 6 ], or more cranial autonomic symptoms associated to the headache [ 7 ], and the response to preventive treatments may vary [ 8 ]. Exogenous factors, such as stress, obesity, intestinal microbiota and even parental behaviour, have been speculated to play a role in the chronification and sensitization process [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%